-54=-9a-27

Simple and best practice solution for -54=-9a-27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -54=-9a-27 equation:


Simplifying
-54 = -9a + -27

Reorder the terms:
-54 = -27 + -9a

Solving
-54 = -27 + -9a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '9a' to each side of the equation.
-54 + 9a = -27 + -9a + 9a

Combine like terms: -9a + 9a = 0
-54 + 9a = -27 + 0
-54 + 9a = -27

Add '54' to each side of the equation.
-54 + 54 + 9a = -27 + 54

Combine like terms: -54 + 54 = 0
0 + 9a = -27 + 54
9a = -27 + 54

Combine like terms: -27 + 54 = 27
9a = 27

Divide each side by '9'.
a = 3

Simplifying
a = 3

See similar equations:

| p=g+5u | | 8(2a-3)=-104 | | 8p+8q= | | .5x^2+2x=3x+7 | | a/6x=5x | | 24/14=m/35 | | 41=-7x+2(-4-32) | | -0.2x(x-6)+x=0.3(4-x) | | -5n+6n+15n-3n=3 | | 50+10t=30 | | -3x(2x+9)=0 | | 4m/3-m/6=-3 | | -45=63+9n | | 99-4x=14x+15 | | F(x)=4(6) | | 7-10x=157-45x | | 6t-54=36 | | r/3+7-r/5=3 | | 5/6(6x-3) | | -12m-24= | | 0.75+2x-1=3x-0.4 | | 7x-6(-x+20)=-224 | | -6y+9=-6y+6 | | F(6)=4x | | (-4.8y+20.1)-(12.7y+9.3)= | | 5p+5=14+4p | | -x+7x-7+2=29+2x+2 | | 55=-138+x | | 10b+15+6b=39 | | 4*2/10 | | (3x+4)(x+5)=0 | | 5x+31=13x-37 |

Equations solver categories